2020
DOI: 10.17503/agrivita.v42i2.2724
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping Farming System and Farmers Income

Abstract: Agriculture cultivation systems and farmer's income are the crucial issues in many agriculture-based developing countries. Our previous study proved that the polyculture system positively affects land productivity and land-use efficiency. This research investigated the relationship between intercropping farming systems and farmer's income. We hypothesized that the intercropping farming system increases farmer's income compared to monoculture. The farming income analysis was carried out using Microsoft Excel an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Parikhani et al (2015) also identified economic factors as important to compliance to GAP. Other authors have also linked GAP to improved income and hence livelihood of smallholders (Jumiyati et al, 2018;Arsyad et al, 2020). The study however disagrees with Olutegbe and Samuel (2020) on the importance of considering relative economic advantage in making choices.…”
Section: Compliance To Gapmentioning
confidence: 90%
See 2 more Smart Citations
“…Parikhani et al (2015) also identified economic factors as important to compliance to GAP. Other authors have also linked GAP to improved income and hence livelihood of smallholders (Jumiyati et al, 2018;Arsyad et al, 2020). The study however disagrees with Olutegbe and Samuel (2020) on the importance of considering relative economic advantage in making choices.…”
Section: Compliance To Gapmentioning
confidence: 90%
“…The result also shows that on the average, the environmental benefit was rated moderate by cocoa farmers. Arsyad et al (2020) also argues that modern agriculture practices have tended to ignore ecological principles thus contributing to unstable sustainable agro-ecosystems. In the same vein, health benefit perceived most by farmers were reduced respiratory problems in humans (mean = 2.25), reduced frequency of disease attack (mean = 2.24) and strong and agile body (mean = 2.21).…”
Section: Perceived Benefits Of Farmers On Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Intercropping can also increase farms benefits due to the large diversity of crops that are mostly grown simultaneously. ARSYAD et al (2020) reported that intercropping farming systems with higher crop diversity greatly increased farmer income. In the southern region of Mexico, little is known about the effect of maize-legume intercropping system on farm income and/or food security; however, a few scientific studies showed that conservation practices can help the small farms confront and adapt to changes and turn the system more resilient.…”
Section: Effect On Farm Income And/or Food Securitymentioning
confidence: 99%
“…Management of habitat using the intercropping system can reduce the level of B. tabaci attacks (Zhang et al, 2020) and the spread of the virus brought by whitefly (Hooks & Fereres, 2006). In general, pest attacks in monocultural planting systems tend to be higher than in the intercropping system (Arsyad et al, 2020;Fattah et al, 2020). Besides that, the ability of B. tabaci to produce eggs (fecundity) (Di et al, 2018) and its survival rate (Zhang et al, 2014) tend to be higher on monocultural condition than the intercropping system.…”
Section: Attack Intensitymentioning
confidence: 99%